miR-223 and Chromogranin A Affect Inflammatory Immune Cell Activation in Liver Metastasis of Neuroendocrine Neoplasms - Lukas Geisler; Katharina Detjen; Teresa Hellberg; Marlene Kohlhepp; Carsten Grötzinger; Jana Knorr; Ines Eichhorn; Raphael Mohr; Theresa Holtmann; Bertram Wiedenmann; Frank Tacke; Christoph Roderburg; et al. (Cells)
Neuroendocrine neoplasms (NENs) are a diverse group originating from endocrine cells/their precursors in pancreas, small intestine, or lung. The key serum marker is chromogranin A (CgA). While commonly elevated in patients with NEN, its prognostic value is still under discussion. Secretion/posttranslational proteolytic cleavage of CgA results in multiple bioactive fragments, which are essential regulators of the cardiovascular and immune system. miR-223, regulator of Nrlp3 inflammasome and neutrophil activation, was recently found to have decreased in patients with NEN. We performed flow cytometry of circulating neutrophils in a patient cohort (n = 10) with NEN, microdissection and histology of tumor tissue. Subsequently, in vitro transfections using the well-established human pancreatic NEN cell line (BON), and co-culture experiments with primary macrophages and neutrophils were performed. Serum miR-223 in patients correlated with the expression of the neutrophil activation marker CD15 in circulating cells. Neutrophilic CD62L/CD63 showed good discrimination compared to healthy controls. Immune cell-derived miR-155, miR-193 and miR-223 colocalize with neutrophil in the extra-tumoral tissue alongside Nlrp3-associated caspase-1 activation. miR-223 knockdown in BON decreased the CgA intracellularly, increased in cellular granularity and caspase-1 activation. Plasmin inhibitor a2-aP reverted those effects. Western Blot showed fragmented CgA following miR-223 knockdown, which altered the inflammatory potential of neutrophils. Our data hence provide initial insights into an immunoregulatory mechanism via miR-223 and CgA in NEN cells, as regulation of miR-223 in NEN may affect tumor-associated inflammation.